Meningkatkan Partisipasi Perempuan dalam Politik di Indonesia: Ceramah dan Diskusi di Majelis Ta’lim Nurkhozin Al-Jaelani, Tangerang Selatan - Ali Noer Zaman; Endang Sulastri; Hilaly Basya; Usni Usni; Muhammad Kosasih; Putri Ade Fitriani; Muhammad Eggy; Marlina Sintyawati (Universitas Pahlawan Tuanku Tambusai, 2023)
Women's participation in politics in Indonesia is a problem that is still being faced by the country and Indonesian community. Even though women have been involved in various problem solving-activities, when viewed from the 2019 election, the number of women’s representative has only reached around 20%, and failed to fulfil 30% quota as stipulated in the law. Various problems hindered the sufficient presence of women in politics including the electoral system in Indonesia, the policies and political will of political parties, and the patriarchal culture that still dominates. To increase awareness of the importance of women's participation in politics, it is necessary to conduct political education. One way is through discussions held at the Nurkhozin Al-Jaelani Ta'lim Assembly, South Tangerang, Banten Province which succeeded in sparking public awareness about the need for women to play a role in politics as evidenced by their responses during the discussion of the issue.